An investigation into the employment generated by new industry locating in Northern Ireland, 1951-80 - Simpson, J. V. (Statistical and Social Inquiry Society of Ireland, 1985)
Implicit in some of the political judgements on the rationale for regional policy is the thesis that the less prosperous regions of the United Kingdom, or indeed any European state, need to be helped by a programme of government assistance towards industrial development which, if it is successful, will eventually reach the point where the new industrial structure will begin to be self sustaining and, possibly, even generate further expansion. In such a thesis there may be arguments for assistance in overcoming the initial diseconomies of locating in a particular region, creating external economies through the interdependence of various projects and increasing the viability of projects as expertise and productivity all improve. All of these might combine to create a more advantageous location which can attract further industry and overcome the initial disadvantages.
Read before the Society, 8 May, 1984
Keywords: Northern Ireland; Industrial development; 314.15